The role of the IFG and pSTS in syntactic prediction: Evidence from a parametric study of hierarchical structure in fMRI. (March 2017) - Matchin, William; Hammerly, Christopher; Lau, Ellen
Abstract: Sentences encode hierarchical structural relations among words. Several neuroimaging experiments aiming to localize combinatory operations responsible for creating this structure during sentence comprehension have contrasted short, simple phrases and sentences to unstructured controls. Some of these experiments have revealed activation in the left inferior frontal gyrus (IFG) and posterior superior temporal sulcus (pSTS), associating these regions with basic syntactic combination. However, the wide variability of these effects across studies raises questions about this interpretation. In an fMRI experiment, we provide support for an alternative hypothesis: these regions underlie top-down syntactic predictions that facilitate sentence processing but are not necessary for building syntactic structure. We presented stimuli with three levels of structure: unstructured lists, two-word phrases, and simple, short sentences; and two levels of content: natural stimuli with real words and stimuli with open-class items replaced with pseudowords (jabberwocky). While both the phrase and sentence conditions engaged syntactic combination, our experiment only encouraged syntactic prediction in the sentence condition. We found increased activity for both natural and jabberwocky sentences in the left IFG ( pars triangularis and pars orbitalis ) and pSTS relative to unstructured word lists and two-word phrases, but we did not find any such effects for two-word phrases relative to unstructured word lists in these areas. Our results are most consistent with the hypothesis that increased activity in IFG and pSTS for basic contrasts of structure reflects syntactic prediction. The pars opercularis of the IFG showed a response profile consistent with verbal working memory. We found incremental effects of structure in the anterior temporal lobe (ATL), and increased activation only for sentences in the angular gyrus (AG)/temporal–parietal junction (TPJ) – both regions showed these effects for stimuli with all real words. These findings support a role for the ATL in semantic combination and the AG/TPJ in thematic processing.